'an actual present alive with multiple futures': narrative, memory and time in Ben Lerner's 10:04. Issue 7 (2nd July 2020) - Bilmes, Leonid
ABSTRACT: This essay reads Ben Lerner's second novel, 10:04, alongside contemporary accounts of narrative time and digital memory technologies, and argues that this narrative reflects on a shift in temporality, whereby present experience is increasingly relegated to future recollection. Bernard Stiegler provides a useful analysis of this situation, as his philosophical account of technics foregrounds memory's reliance on technology, whereby the present is increasingly archived as a future memory. Stiegler also insists that every tool carries within itself a capacity for re-invention and projection into different futures, and this essay reads narrative form in this sense of an inventive technics capable of projecting us not into actual futures, but into a sense of future possibility. Lerner's narrator may be read as seeking to open up the future by revisiting possibilities which his past self once imagined, and also by imagining future moments of retrospect from which he will one day have recounted his experience. It is in the mode of the anticipation of retrospection that a sense of the future is kept open in this novel, despite the temporally foreclosed structure of an already written narrative.